Резонансный формирователь наносекундных сверхвысокочастотных импульсов - Новиков С. А. Сергей Автономович (1991, 1991)
The device, which is designed for shaping nanosecond SHF pulses in radiolocation when scanning the Earth surface layers, as well as for plasma experimental investigations under laboratory conditions, is described. The device performance is based on microsecond SHF pulse time compression by means of a resonator in the form of a coaxial line section.